Alternating-current electroluminescent device and preparation method thereof

By using a quantum dot layer composed of polymer polymer and perovskite quantum dots in the electro-optic sheet, combined with the electrode layer and the dielectric layer, the problems of increasing the thickness of the existing electro-optic sheet material and insufficient water and oxygen resistance are solved, and an efficient and stable AC field luminescence effect is achieved.

CN119653978APending Publication Date: 2025-03-18NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411829499.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The luminescent layer material of the existing electro-optic sheet is phosphor particles, which leads to an increase in the thickness of the luminescent film and insufficient water and oxygen resistance, making it impossible to effectively utilize the high luminescent conversion efficiency of perovskite quantum dot materials.

Method used

A quantum dot layer composed of polymer and perovskite quantum dots is adopted, combining the electrode layers on both sides and the dielectric layer in the middle, and the layer thickness and flatness are accurately adjusted through slit coating, and the coating process is optimized to improve the uniformity and adhesion of the quantum dot film.

Benefits of technology

The toughness and flatness of the quantum dot layer have been significantly improved, and a quantum dot-type electroluminescent device has been successfully constructed, which can emitting light stably under the action of an alternating electric field, with high luminescence conversion efficiency, stability and strong water and oxygen resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653978A_ABST
    Figure CN119653978A_ABST
Patent Text Reader

Abstract

The invention discloses an alternating-current electroluminescent device and a preparation method thereof. The alternating-current electroluminescent device comprises a first electrode layer, an optional dielectric layer, a quantum dot layer and a second electrode layer which are sequentially arranged in a stacked mode, and the two faces of the quantum dot layer are in direct contact with the dielectric layer and the second electrode layer respectively. The quantum dot layer comprises perovskite quantum dots and a high-molecular polymer. According to the device, the toughness and the flatness of the quantum dot layer are remarkably improved, so that the quantum dot type electroluminescent device is successfully constructed, and stable luminescence under the action of an alternating electric field can be realized; besides, according to the preparation method provided by the invention, the thickness and the flatness of the quantum dot layer are accurately regulated and controlled through slit coating, and the uniformity and the adhesive force of the quantum dot film are remarkably improved by optimizing a coating process, so that electroluminescence under the action of an alternating electric field can be stable, and the quantum dot film is prepared. The method is also a key for realizing successful preparation of the quantum dot type alternating-current electroluminescent device and realizing stable alternating-current electroluminescent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of light emitting devices, and in particular to an alternating current electroluminescent device and a preparation method thereof. Background Art

[0002] The electro-optical film is an advanced field-induced luminescent device. Its principle is to excite the fluorescent material through the alternating electric field generated by the alternating voltage applied to the electrodes at both ends. The electrons in the fluorescent material are excited by the electric field and emit light with high efficiency in the form of energy radiation. In view of the high efficiency of the luminescence process and the fact that it is different from thermal radiation luminescence, some people also call it cold light.

[0003] The structure of an electro-optical sheet is usually: a light-emitting layer; there are transparent electrode layers on both sides of the light-emitting layer, the transparent electrode layers are connected to a power source, and high-frequency alternating current is used to form an alternating electric field in the light-emitting layer. Under the stimulation of the alternating electric field, the light-emitting layer emits light. In order to improve the water and oxygen resistance of the light-emitting layer, a transparent protective layer is usually coated on the outside of the transparent electrode layer to block water and oxygen, prevent leakage current, etc. The electro-optical sheet can achieve surface luminescence, and has the advantages of no heat generation, small size, low energy consumption, long life, no glare, and high luminous efficiency, so it can be widely used. In addition, the flexible and thin structural characteristics can introduce waterproof and pressure-resistant packaging films to achieve various advantages such as color change, shock resistance and waterproofness, and odorless and fold-resistant. As a result, electro-optical sheets have been widely used in many fields at present.

[0004] However, the light-emitting layer of most existing electro-optical films is composed of phosphor particles, which are relatively large in size, resulting in an increase in the thickness of the light-emitting film. In addition, under packaging structures such as PET and PVC, the water and oxygen resistance of the light-emitting material is insufficient, which easily leads to protection defects during the packaging process.

[0005] Specifically, most electro-optical films currently prepared in the industry use ZnS:Mn, Cu phosphors as the material of the light-emitting layer. In theory, perovskite quantum dot materials have higher luminescence conversion efficiency, thanks to their unique quantum confinement effect, which can achieve more efficient light emission under smaller excitation energy. However, electro-optical films using perovskite quantum dots have not yet been successfully developed.

[0006] At the same time, in other fields, the use of perovskite quantum dots as photoluminescent quantum dot filters is a hot topic in the industry. It has been successfully developed and applied to the backlight source of LCD displays, which can obtain a wider color gamut and a higher contrast display effect than LED backlight sources. Although it can be used in the field of high-end displays, its complex preparation process limits its widespread application. Summary of the invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide an AC electroluminescent device and a method for preparing the same.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0009] In the first aspect, the present invention provides an AC electroluminescent device, which comprises a first electrode layer, a dielectric layer that may or may not be provided, a quantum dot layer, and a second electrode layer that are stacked in sequence, and the two sides of the quantum dot layer are in direct contact with the dielectric layer and the second electrode layer respectively; the quantum dot layer comprises perovskite quantum dots and a high molecular polymer, and the surface of the perovskite quantum dots is bound with molecules of a polar solvent. Specifically, the quantum dot layer comprises a film layer matrix formed by a high molecular polymer and perovskite quantum dots dispersed between the high molecular polymers.

[0010] In a second aspect, the present invention further provides a method for preparing an AC electroluminescent device, comprising:

[0011] forming a first electrode layer and a dielectric layer on a surface of the substrate;

[0012] Using a coating liquid to coat the surface of the dielectric layer to form a precursor layer, wherein the coating liquid contains perovskite quantum dots and a high molecular polymer, and the solvent is a polar solvent and does not contain an acidic component;

[0013] Thermally treating the precursor layer to volatilize and remove the solvent therein, thereby forming a quantum dot layer;

[0014] A second electrode layer is formed at least on the surface of the quantum dot layer.

[0015] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include:

[0016] The AC electroluminescent device provided by the present invention significantly improves the toughness and flatness of the quantum dot layer by setting electrode layers on both sides, a dielectric layer in the middle, and a quantum dot layer composed of a high molecular polymer and perovskite quantum dots, thereby successfully constructing a quantum dot-type electroluminescent device that can achieve stable luminescence under the action of an AC electric field.

[0017] In addition, the preparation method provided by the present invention can precisely control the thickness and flatness of the quantum dot layer through slit coating, and significantly improve the uniformity and adhesion of the quantum dot film by optimizing the coating process, so that the field light emission under the action of the AC electric field can be stable, which is also the key to successfully preparing quantum dot-type AC field light-emitting devices and achieving stable AC field light emission.

[0018] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic structural diagram of an AC electroluminescent device provided by a typical implementation case of the present invention;

[0020] Figure 2 is a schematic structural diagram of an AC electroluminescent device provided by another typical embodiment of the present invention;

[0021] Figure 3a This is a photo of the luminous state of an AC electroluminescent device provided in a typical implementation case of the present invention;

[0022] Figure 3b This is an enlarged photo of the luminous state of an AC electroluminescent device provided in a typical embodiment of the present invention;

[0023] Figure 4a is a photo of the luminous state of an AC electroluminescent device provided by another typical embodiment of the present invention;

[0024] Figure 4b This is an enlarged photo of the light-emitting state of an AC electroluminescent device provided in another typical embodiment of the present invention;

[0025] Figure 5 It is a physical photo of an AC electroluminescent device provided in a typical implementation case of the present invention;

[0026] Figure 6 It is a schematic diagram of the structural design of an AC electroluminescent device provided in a typical implementation case of the present invention. DETAILED DESCRIPTION

[0027] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0029] Moreover, relational terms such as “first” and “second” are merely used to distinguish one component or method step from another with the same name, but do not necessarily require or imply any such actual relationship or order between these components or method steps.

[0030] An embodiment of the present invention provides an AC electroluminescent device, which includes a first electrode layer, a dielectric layer that may or may not be provided, a quantum dot layer, and a second electrode layer that are stacked in sequence, and the two sides of the quantum dot layer are directly in contact with the dielectric layer and the second electrode layer respectively; the quantum dot layer contains perovskite quantum dots and a high molecular polymer, and the surface of the perovskite quantum dots is bound to molecules of a polar solvent.

[0031] The AC electroluminescent device provided by the present invention is different from the quantum dot LED, which does not utilize the composite luminescence mechanism of holes and electrons. In the prior art, in order to achieve high brightness, long life, and high color purity electroluminescence, OLED film can achieve similar effects, through the complex structure of electron injection layer / electron transport layer / quantum dot layer / hole transport layer / hole injection layer, to achieve the recombination of electrons and holes in the light-emitting layer, thereby achieving DC electroluminescence. The thickness of a single layer of OLED film is 30-80nm. In view of its principle of direct current driven luminescence, there is a serious mismatch between the rates of hole injection and electron injection, so it is necessary to achieve carrier balance through a multilayer structure. This structure determines that the raw material purity is high. If a wide-width light-emitting panel needs to be prepared, a large-size evaporation technology must be used. The complex manufacturing process brings the disadvantages of high cost and low yield, and it is impossible to achieve a high-capacity, low-cost and rapid production method. Although OLED film can also achieve high brightness and long life electroluminescence, its complex multilayer structure and high-cost manufacturing process limit its application in large-scale production.

[0032] In the present invention, the luminescence principle used is similar to that of the electro-optical sheet made of fluorescent materials, which is mainly the field luminescence phenomenon of perovskite quantum dot materials caused by AC electric field. Unlike the simple luminescence of traditional fluorescent materials, the conditions required for AC field luminescence of perovskite quantum dots are more stringent. Specifically, AC field luminescence devices emit light based on the characteristics of perovskite quantum dots under AC electric field. When the AC electric field acts on the perovskite quantum dots in the quantum dot layer, the electrons are driven by the electric field force to accelerate, and they transition from the ground state to the excited state due to the quantum confinement effect. However, due to factors such as the small size of the quantum dots, there are few overheated electrons and insufficient effective collisions, making it difficult to emit light stably and efficiently. At this time, the small amount of polar molecules remaining in the quantum dot layer form "quasi-ligands", which provide an acceleration "runway" for electrons and promote electronic excitation. The coupling effect between them and the electrons and the change of their own polarization orientation coordinate the movement of electrons and accelerate the migration of carriers. At the same time, polar solvents dissolve high molecular polymers to facilitate film formation, interact with quantum dots to optimize their microscopic environment, adjust electrical properties, reduce energy loss, and improve luminescence efficiency.

[0033] In addition, the composite structure of the quantum dot layer can enhance toughness and flatness, ensure uniform distribution of quantum dots and good interface contact, and improve energy conversion efficiency. Compared with traditional electro-optical sheets, the overall device has high luminescence conversion efficiency, strong stability and water and oxygen resistance, and excellent color purity. The preparation process ensures uniform thickness and good adhesion of the quantum dot layer, reduces the starting voltage, is conducive to light and flexible design, and has potential application prospects in many fields.

[0034] As for some specific structural features, in some embodiments, at least the second electrode layer is made of a transparent material to achieve the extraction of light emitted by the electro-optical sheet.

[0035] In some embodiments, the second electrode layer wraps the sidewalls of the quantum dot layer and the dielectric layer; preferably, in some embodiments, a gate electrode is disposed on the surface of the second electrode layer, and the specific structure is as follows: Figure 1 shown.

[0036] In some embodiments, the AC electroluminescent device further comprises a transparent barrier layer encapsulating the first electrode layer, the dielectric layer, the quantum dot layer and the second electrode layer. The specific structure is as follows: Figure 2 shown.

[0037] In addition, regarding specific composition and microstructure parameters, in some embodiments, the thickness of the quantum dot layer is 2-20 μm.

[0038] In some embodiments, in the quantum dot layer, the mass fraction of the perovskite quantum dots is 1-30%.

[0039] In some embodiments, the perovskite quantum dots have a diameter of 2-30 nm.

[0040] In some embodiments, the number average molecular weight of the high molecular weight polymer is 5,000-50,000.

[0041] As for the specific material selection, in some embodiments, the perovskite quantum dots include any one or a combination of two or more of inorganic perovskite, methylamine perovskite, aniline perovskite, and long-chain perovskite.

[0042] In some embodiments, the inorganic perovskite is represented by CsPbX3, wherein X=Cl, Br, I.

[0043] In some embodiments, the methylamine perovskite is represented as CH3NH3AX3, wherein A=Ge, Sn, Pb, Bi, Mn; X=Cl, Br, I.

[0044] In some embodiments, the aniline perovskite includes any one of (C6H5NH3)2PbBr4, (C6H5NH3)2PbCl4, or a combination of both.

[0045] In some embodiments, the long-chain perovskite is represented by (RNH3)2AX4, wherein R represents a long-chain organic molecular group; A=Ge, Sn, Pb, Bi, Mn; X=Cl, Br, I.

[0046] In some embodiments, the polymer includes any one of cellulose acetate, polyvinylidene fluoride, polycarbonate, polyvinyl carbonate, or a combination of two or more thereof.

[0047] In some embodiments, the material of the dielectric layer includes any one of TiO2, SiO2, BaTiO3, or a combination of two or more thereof.

[0048] Regarding other structures, in some embodiments, the AC electroluminescent device further includes an AC driving chip, and two output terminals of the AC driving chip are electrically connected to the first electrode and the second electrode respectively.

[0049] In some more specific embodiments, the frequency of the AC drive chip is 800Hz-60kHz, and the voltage is 60-160V.

[0050] And regarding the waveform, in some more specific embodiments, the driving waveform of the AC driving chip includes any one of a square wave, a sine wave, and a triangle wave, and the positive and negative waveforms are the same.

[0051] As some typical examples of the above technical solutions, the AC electroluminescent device provided in the embodiments of the present invention has a stacked structure from bottom to top, which is: substrate, Ag / Al electrode coating, TiO2 / BaTiO3 dielectric coating, quantum dot layer, transparent electrode, and gate line electrode.

[0052] Among them, the electrode coating can be coated with commercially available silver paste or silver aluminum paste, and then baked to form a bottom electrode; the dielectric coating can be made of commercially available TiO2, SiO2 or BaTiO3 particles, which are mixed and stirred with cellulose acetate, polycarbonate, and polyvinyl carbonate, and then coated on the electrode coating by a slit coating method and baked in an oven. The mass ratio of the particles to the polymer can be 1:0.4-3, and the curing temperature is, for example, 80°C-120°C, and the time is 20-30 minutes; the preparation of the quantum dot layer can be achieved by slit coating the quantum dot coating liquid and then thermally drying it; the transparent conductive electrode can be Pedot:PSS, which is coated with a slit coater, and then commercially available silver paste is used to apply a patterned gate by screen printing, and a top electrode is formed after drying, and then the pins of the top electrode and the bottom electrode are bonded to the AC drive chip to form a quantum dot electro-optical sheet.

[0053] In order to obtain the above-mentioned AC electroluminescent device, a second aspect of the embodiment of the present invention further provides a method for preparing the AC electroluminescent device, which comprises the following steps:

[0054] forming a first electrode layer and a dielectric layer on a surface of the substrate;

[0055] Using a coating liquid to coat the surface of the dielectric layer to form a precursor layer, wherein the coating liquid contains perovskite quantum dots and a high molecular polymer, and the solvent is a polar solvent and does not contain an acidic component;

[0056] Thermally treating the precursor layer to volatilize and remove the solvent therein, thereby forming a quantum dot layer;

[0057] A second electrode layer is formed at least on the surface of the quantum dot layer.

[0058] In some embodiments, the coating of the precursor layer is carried out by slit coating, and the thickness of the precursor layer is controlled so that the thickness of the quantum dot layer is less than 20 μm.

[0059] As some typical examples of the above technical solutions, the exemplary preparation process provided by the present invention uses perovskite quantum dot materials as light-emitting bodies, mixes them with high molecular polymer molecules and solvents to form a quantum dot coating liquid, and then uses a slit coating technology to coat it on the dielectric insulating layer. After heating and curing, a quantum dot film is formed. Subsequently, a transparent conductive electrode is coated on the quantum dot film and an AC power supply is bonded to realize the preparation of a quantum dot electroluminescent panel.

[0060] Generally, DC-driven perovskite quantum dot LED devices have high brightness, are expensive to manufacture, and are mostly used for information display. However, the AC-driven field-induced luminescent electro-optical film targeted by the present invention has low brightness, simple manufacturing structure, and can be used for surface light sources, such as traffic signs.

[0061] In the present invention, the preparation and film formation of the coating liquid are critical. If the coating property is not good, stable electro-optical output cannot be achieved. Specifically, if the coating liquid components are not properly selected, the perovskite material will be corroded. Therefore, the coating liquid selected in the present invention is completely non-acidic and very friendly to ionic materials, which can ensure that the perovskite is not distorted. In addition, regarding the coating conditions, slight coating defects are also factors that can easily lead to field luminescence failure. Therefore, in the present invention, a slit coating method is required to accurately control the layer thickness and film defects.

[0062] In addition, the selection of a suitable polar solvent is also critical. Polar solvents can form ligands on the surface of quantum dots. The main force between the ligands and quantum dots is the coordination bond. Specifically, quantum dots are nanoscale semiconductor crystals with many dangling bonds on their surface atoms and high activity. Polar solvent molecules as ligand molecules have lone pairs of electrons and can interact with the empty orbitals of metal atoms on the surface of quantum dots to form coordination bonds, which can effectively passivate the surface of quantum dots and reduce surface defects. In addition, there are van der Waals forces. The intermolecular van der Waals forces between ligands and quantum dots will affect the adsorption, arrangement and other interactions between them. Therefore, even after the coating and heat treatment stages, a certain amount of polar solvent molecules will remain on the surface of perovskite quantum dots, which is critical for the formation of efficient AC field luminescence. It was also observed in the actual preparation process that it is difficult to form very bright AC field luminescence if a pure non-polar solvent is used to achieve coating. Suitable polar solvents include any one or more combinations of amides, sulfones, and esters, but are not limited to this. Polar solvents that can effectively bind to quantum dots are all included in this list.

[0063] In some embodiments, the mass ratio of the perovskite quantum dots, the high molecular polymer and the solvent in the coating solution is 0.1-0.6:20-100:80-60.

[0064] In some embodiments, the high molecular polymer in the coating solution comprises at least two different high molecular materials.

[0065] In some embodiments, the method for preparing the coating solution specifically comprises the following steps:

[0066] mixing the perovskite quantum dots with a solvent to form a dispersion;

[0067] The dispersion liquid is mixed with a high molecular polymer to form the coating liquid.

[0068] In some embodiments, the heat treatment includes a first treatment stage and a second treatment stage, wherein the temperature of the first treatment stage is 75-85°C and the time is 20-40 min, and the temperature of the second treatment stage is 110-130°C and the time is 15-25 min.

[0069] In the preparation process of the present invention, the annealing process also has a great impact on whether the film layer can successfully achieve stable electroluminescence. The present invention preferably adopts a two-stage annealing process, which can avoid microscopic damage to the film layer, thereby ensuring stable electroluminescence. However, the use of ordinary annealing processes is very likely to cause microscopic defects that are difficult to distinguish with the naked eye. These defects will cause the electric field to concentrate and fail to act evenly on the entire surface, making it difficult to produce stable electroluminescence.

[0070] As some typical examples of the above technical solutions, the above coating solution can be prepared by the technical solutions described below:

[0071] (1) Raw material preparation

[0072] Perovskite quantum dot particles can be made of a variety of particle materials, such as: ① Inorganic materials: CsPbX3 (X = Cl, Br, I), etc.; ② Methylamines: CH3NH3AX3 (A = Ge, Sn, Pb, Bi, Mn; X = Cl, Br, I), such as CH3NH3PbCl3, CH3NH3PbBr3, CH3NH3PbI3, CH3NH3GeCl3, CH3NH3GeBr3, CH3NH3GeI3, CH3NH3SnCl3, CH 3NH3SnBr3, CH3NH3BiCl3, CH3NH3BiBr3, CH3NH3BiI3, CH3NH3MnCl3, CH3NH3MnBr3, CH3NH3MnI3; ③Aniline: (C6H5NH3)2PbBr4, (C6H5NH3)2PbCl4, etc.; ④Long chain: (RNH3)2AX4 (here R represents a long chain organic molecule group; A=Ge, Sn, Pb, Bi, Mn; X=C1, Br, I).

[0073] High molecular polymer: cellulose acetate, polyvinylidene fluoride, polycarbonate, polyvinyl carbonate, etc.;

[0074] Solvents: dimethyl sulfoxide, N,N-dimethylformamide, trimethyl phosphate, N-methylpyrrolidone, triethyl phosphate, dimethylacetamide, N-ethylacetamide, etc.

[0075] (2) Formula preparation, the formula is shown in the following table:

[0076] Perovskite quantum dot particles 0.1~0.6 units High molecular weight polymer 20~100 units Solvent 80~160 units

[0077] The perovskite quantum dot particles are synthesized by chemical methods and purified, dispersed into a solvent, and fully stirred to form a solution A for use. 2-3 kinds of high molecular polymers are fully stirred to form a slurry B. Solution A and slurry B are fully mixed in a mass ratio of 1:0.5 to 1:2 to form a quantum dot coating liquid. The quantum dot coating liquid is coated on the dielectric layer by slit coating to form a thick film of 1 to 20 microns, and then dried in an oven. The oven settings are: temperature 80°C, 30 minutes, temperature 120°C, time 20 minutes. After drying, it is naturally cooled to form a quantum dot layer.

[0078] As a typical example, the specific process of the above preparation method can be as follows:

[0079] 1. Form a first electrode layer and a dielectric layer on the surface of the substrate.

[0080] 2. Prepare coating solution: dissolve high molecular polymer in polar solvent (one or more combinations can be selected from N, N-dimethylformamide, dimethyl sulfoxide, trimethyl phosphate, N-methylpyrrolidone, triethyl phosphate, dimethylacetamide, N-ethylacetamide, γ-butyrolactone, cyclopentane sulfone, propylene carbonate) to form polymer solution, mix perovskite quantum dots with another part of polar solvent to form dispersion, and then mix the two to obtain coating solution, wherein the mass ratio of perovskite quantum dots, high molecular polymer and solvent is 0.1-0.6:20-100:80-160, and the high molecular polymer contains at least 2 kinds.

[0081] 3. Use the coating liquid to slit-coat the surface of the dielectric layer to form a precursor layer, and control the thickness so that the quantum dot layer is less than 20 μm.

[0082] 4. The precursor layer is heat treated (in two stages: 80°C for 30 min and 120°C for 20 min) to remove the solvent and form a quantum dot layer.

[0083] 5. Form a second electrode layer at least on the surface of the quantum dot layer.

[0084] The AC electroluminescent device obtained by the above technical solution can not only provide thinner size, higher brightness and longer service life, but also can realize autonomous light emission through electric drive compared with photoluminescent quantum dot filter, and obtain more convenient application fields. Compared with traditional electro-optical film, the advantages are listed as follows:

[0085] 1. The luminescence performance of quantum dot materials is better than that of ZnS:Mn, Cu or ZnS:Cu phosphors used in electro-optical films, with higher conversion efficiency, stronger stability and water and oxygen resistance.

[0086] 2. The particle size of quantum dot materials is more uniform, at the nm level, which is much smaller than the commonly used phosphors of 5-50μm. This determines that when forming the light-emitting layer, the light-emitting layer is thinner, at 2μm-20μm.

[0087] 3. The full width at half maximum of the luminescence of quantum dot materials is very small, and the slit width is ≤20-50nm, which is better than the 80-220nm of commonly used phosphors. The excellent color purity can be used more widely in displays.

[0088] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.

[0089] Example 1

[0090] This embodiment illustrates a preparation process of a perovskite quantum dot electro-optical sheet, which is specifically as follows:

[0091] Using PET as the substrate, a bottom electrode layer is formed by coating with silver paste and drying;

[0092] A dielectric layer with a thickness of 20 μm is formed on the surface of the lower electrode layer by slit coating. The dielectric layer coating comprises a slurry of BaTiO3 particles and polycarbonate mixed in N-methylpyrrolidone in a mass ratio of 1:1.

[0093] The quantum dot layer is formed on the surface of the dielectric layer by slit coating. The specific ratio and process are as follows:

[0094] Ratio / g Perovskite quantum dots 0.5 N-Methylpyrrolidone 170 Polyvinylidene fluoride: cellulose acetate = 1: 2.1 60

[0095] The preparation method is as follows: the mass ratio of polyvinylidene fluoride to cellulose acetate is 1:2.1, which is dissolved in a mixed solvent composed of N-methylpyrrolidone and γ-butyrolactone (the mass ratio can be adjusted according to actual conditions, such as 3:1) to form a polymer solution, and dispersed in another part of a mixed solvent composed of N-methylpyrrolidone and γ-butyrolactone (the mass ratio can be adjusted according to actual conditions, such as 2:1) to form a dispersion liquid according to the ratio in the table, and the two are mixed and stirred for 30 minutes (through dry air protection) to form a coating liquid. Pour the quantum dot coating liquid into the liquid supply pump of the slit coater, apply it to the dielectric layer film, and dry it in an oven. The oven settings are: temperature 80°C, 30 minutes, temperature 120°C, time 20 minutes. A quantum dot luminescent film that can be used for AC field luminescence can be formed.

[0096] Pedot:PSS is used on the surface of the quantum dot layer and coated with a slit coater to form a transparent conductive electrode. Commercially available silver paste is then used to apply a patterned gate by screen printing. After drying, a top electrode is formed. The pins of the top electrode and the bottom electrode are then bonded to an AC drive chip to form a quantum dot electro-optical sheet.

[0097] In the above preparation process, the viscosity of the prepared quantum dot coating liquid is 840CP. After slit coating, the luminescent effect of the electroluminescent device is as follows: Figure 3a and Figure 3b As shown, obvious green electroluminescence can be seen.

[0098] Example 2

[0099] This embodiment also illustrates a preparation process of a perovskite quantum dot electro-optical sheet, which is specifically as follows:

[0100] A glass sheet is used as a substrate, and a silver-aluminum paste is applied and dried to form a bottom electrode layer;

[0101] No dielectric layer is provided.

[0102] Dissolve polyvinylidene fluoride in a mixed solvent (mass ratio of 1:1.5) consisting of ethylene carbonate and cyclopentane sulfone (the mass ratio can be adjusted according to actual conditions, such as 1:1) to form a polymer solution, disperse 0.6 g of quantum dots in a mixed solvent of N,N-dimethylformamide: dimethyl sulfoxide: propylene carbonate (the mass ratio can be adjusted according to actual conditions, such as 2:1:1) to form a dispersion, mix and stir the two for 30 minutes, then let stand for 24 hours to remove bubbles to form a coating solution, and then slit coat, dry (80°C for 30 minutes, 120°C for 20 minutes) and cool to form a quantum dot light-emitting layer.

[0103] Pedot:PSS is used on the surface of the quantum dot layer and coated with a slit coater to form a transparent conductive electrode. Commercially available silver paste is then used to apply a patterned gate by screen printing. After drying, a top electrode is formed. The pins of the top electrode and the bottom electrode are bonded to an AC drive chip to form a quantum dot electro-optical sheet. The frequency of the AC drive chip is 20kHz and the voltage is 80V.

[0104] The viscosity of the quantum dot coating liquid prepared in the above embodiment is 460CP. After slit coating, an electroluminescent device is prepared, and its luminous effect is as follows: Figure 4a and Figure 4b As shown, obvious green electroluminescence can be seen.

[0105] In the above two embodiments, the device photos after the quantum dot coating liquid is dried are as follows: Figure 5 As shown, the graphic design diagram is as follows Figure 6 As shown, of course, even if the specific design is different from that shown in the figure, the same function can be achieved by using a similar multi-layer structure.

[0106] Comparative Example 1

[0107] A glass sheet is used as a substrate, and silver-aluminum paste is coated and dried to form a bottom electrode layer without a dielectric layer.

[0108] The slit-coated quantum dot layer has the following ratios: 0.6 g perovskite quantum dots, 120 g N,N-dimethylformamide: dimethyl sulfoxide = 1:0.6, polyvinylidene fluoride: ethylene carbonate = 1:1.5, 30 g. Preparation method: quantum dots are dispersed in a mixed solvent to form solution A, polyvinylidene fluoride is dissolved in ethylene carbonate to form slurry B, the two are mixed and stirred for 30 minutes, and then allowed to stand for 24 hours to remove bubbles to form a coating solution, which is then dried (80°C for 30 minutes, 120°C for 20 minutes) and cooled to form a quantum dot light-emitting layer.

[0109] The subsequent electrode formation steps are the same as in Example 1, and a quantum dot electro-optical sheet (AC drive chip frequency 20KHz, voltage 80V) is obtained. The viscosity of the quantum dot coating liquid is 460CP.

[0110] Compared with Chinese invention patents such as CN107966852A, the quantum dot film in the present invention mainly improves the water and oxygen isolation performance by means of high barrier polymers and covering barrier layers. Although the present invention does not set a dielectric layer in this step, it has unique advantages in AC electroluminescence performance through the synergistic effect of the subsequent quantum dot layer and other layers and the unique quantum dot layer composition. Compared with Chinese invention patents such as CN107394014B, although there are some similar operations in the preparation process of the quantum dot coating liquid, the quantum dot material of the present invention is perovskite quantum dots, and the entire device structure and the final application in AC electroluminescence are different from the LED quantum dot coating liquid application scenario of the patent. The present invention aims to achieve stable and efficient AC electroluminescence.

[0111] Comparative Example 2

[0112] This comparative example is similar to Example 1, but the quantum dot layer is coated by conventional spin coating. Due to the viscosity characteristics of the quantum dot coating solution in the present invention (which can be combined with the viscosity caused by the ratio of quantum dots, polymers and solvents mentioned above), when the spin coating method is used, the film thickness and uniformity cannot be effectively controlled, resulting in radial protrusions on the surface, cracks after drying, and inability to achieve effective AC field luminescence.

[0113] Compared with the film-forming processes that may be involved in Chinese invention patents such as CN107394014A, the composition and characteristics of the quantum dot layer of the present invention determine that the traditional spin coating method is not applicable, and the patent may not involve the problems that arise when the specific quantum dot layer of the present invention is spin-coated. Compared with Chinese invention patents such as CN107966852A, the process used can successfully prepare a quantum dot film with certain properties, while the present invention cannot achieve a similar film-forming effect when not using a suitable slit coating process, which further proves the uniqueness and advantages of the process of the present invention.

[0114] Comparative Example 3

[0115] This comparative example is similar to Example 1, but the quantum dot layer is dried at 100°C for 50 minutes after coating (which is different from the optimized heat treatment process in the examples of the present invention, such as the two-stage heat treatment at 80°C for 30 minutes and 120°C for 20 minutes in Example 1, and is also different from the drying or heat treatment processes that may be involved in other patents. For example, Chinese invention patents such as CN107394014B may not clearly involve the effect of this temperature and time combination on film performance). Because the components in the quantum dot layer of the present invention (such as high molecular polymers, polar solvents, etc.) undergo adverse physical or chemical changes under such inappropriate drying conditions, resulting in cracking and shedding of the film surface, the film cannot form effective field-induced luminescence, and there is odor emission. It can be seen that the heat treatment process of the present invention is very critical to maintaining the film performance.

[0116] The present invention clarifies the serious impact of inappropriate drying conditions on the performance of quantum dot layer films through comparative examples, and the patent focuses on the preparation process of quantum dot coating liquid. Compared with Chinese invention patents such as CN107966852A, the quantum dot film in the present invention has certain advantages in stability. The present invention illustrates through this comparative example that if the correct heat treatment process is not adopted, similar stability cannot be achieved, thereby reflecting the optimization of the heat treatment process of the present invention and its important contribution to the overall performance of the device.

[0117] Based on the above embodiments and comparative examples, it can be clearly seen that:

[0118] 1. The slit coating method adopted in the present invention can not only realize the preparation of large-area thin films, but also significantly improve the uniformity and adhesion of the quantum dot film by optimizing the coating process.

[0119] 2. Disperse perovskite quantum dots in polyvinylidene fluoride, cellulose acetate, polycarbonate, and polyvinyl carbonate, heat them to 80°C to 120°C to reduce the viscosity, and use polymers as adhesives for film formation. This can greatly improve the flexibility of light-emitting devices and significantly improve the film flatness and consistency of the devices.

[0120] 3. In order to improve the solubility of perovskite quantum dots in polymer molecules, the quantum dots must first be dispersed in a solvent. The choice of solvent will allow the quantum dot layer to dry quickly without producing large bubbles, thereby avoiding short circuits during device operation.

[0121] Finally, the AC electroluminescent device provided in the embodiment of the present invention significantly improves the toughness and flatness of the quantum dot layer by setting electrode layers on both sides, a dielectric layer in the middle, and a quantum dot layer composed of high molecular polymers and perovskite quantum dots, thereby successfully constructing a quantum dot-type electroluminescent device that can achieve stable luminescence under the action of an AC electric field.

[0122] The present invention not only improves the uniformity and adhesion of the quantum dot film, but also effectively improves the local migration effect of carriers under an AC electric field, thereby significantly improving the luminescence performance by carefully selecting the type of polar solvent and optimizing its application in the preparation process, combined with the slit coating method and other process steps.

[0123] In summary, the present invention successfully constructs a quantum dot-type electroluminescent device, which shows obvious advantages in flexibility, flatness, consistency and luminous efficiency, and provides a more competitive technical solution in the field of AC electroluminescent device technology.

[0124] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An AC electroluminescent device, characterized in that: It comprises a first electrode layer, a dielectric layer which may or may not be provided, a quantum dot layer and a second electrode layer which are stacked in sequence, and two sides of the quantum dot layer are in direct contact with the dielectric layer and the second electrode layer respectively; The quantum dot layer comprises perovskite quantum dots and high molecular polymer, and the surface of the perovskite quantum dots is combined with molecules of a polar solvent.

2. The AC electroluminescent device according to claim 1, characterized in that: At least the second electrode layer is made of a transparent material; And / or, the second electrode layer wraps the side walls of the quantum dot layer and the dielectric layer; a gate line electrode is provided on the surface of the second electrode layer; And / or, the AC electroluminescent device further includes a transparent barrier layer wrapping the first electrode layer, the dielectric layer, the quantum dot layer and the second electrode layer.

3. The AC electroluminescent device according to claim 1, characterized in that: The thickness of the quantum dot layer is 2-20 μm; and / or, in the quantum dot layer, the mass fraction of the perovskite quantum dots is 1-30%; And / or, the diameter of the perovskite quantum dots is 2-30 nm; And / or, the number average molecular weight of the high molecular weight polymer is 5000-50000.

4. The AC electroluminescent device according to claim 1, characterized in that: The perovskite quantum dots include any one or a combination of two or more of inorganic perovskite, methylamine perovskite, aniline perovskite, and long-chain perovskite; The inorganic perovskite is represented by CsPbX3, wherein X=C1, Br, I; And / or, the methylamine perovskite is represented by CH3NH3AX3, wherein A=Ge, Sn, Pb, Bi, Mn; X=Cl, Br, I; And / or, the aniline perovskite includes any one of (C6H5NH3)2PbBr4, (C6H5NH3)2PbCl4 or a combination of two thereof; And / or, the long-chain perovskite is represented by (RNH3)2AX4, wherein R represents a long-chain organic molecular group; A=Ge, Sn, Pb, Bi, Mn; X=Cl, Br, I.

5. The AC electroluminescent device according to claim 1, characterized in that: The polymer includes any one or a combination of two or more of cellulose acetate, polyvinylidene fluoride, polycarbonate, and polyvinyl carbonate; And / or, the material of the dielectric layer includes any one of TiO2, SiO2, BaTiO3 or a combination of two or more thereof.

6. The AC electroluminescent device according to claim 1, characterized in that: It also includes an AC drive chip, wherein two output terminals of the AC drive chip are electrically connected to the first electrode and the second electrode respectively; The frequency of the AC drive chip is 800Hz-60kHz, and the voltage is 60-160V; And / or, the driving waveform of the AC driving chip includes any one of a square wave, a sine wave, and a triangle wave, and the positive and negative waveforms are the same.

7. A method for preparing an AC electroluminescent device, characterized in that: include: forming a first electrode layer and a dielectric layer on a surface of the substrate; Using a coating liquid to coat the surface of the dielectric layer to form a precursor layer, wherein the coating liquid contains perovskite quantum dots and a high molecular polymer, and the solvent is a polar solvent and does not contain an acidic component; Thermally treating the precursor layer to volatilize and remove the solvent therein, thereby forming a quantum dot layer; A second electrode layer is formed at least on the surface of the quantum dot layer.

8. The preparation method according to claim 7, characterized in that: The coating of the precursor layer is carried out by slit coating, and the thickness of the precursor layer is controlled so that the thickness of the quantum dot layer is less than 20 μm.

9. The preparation method according to claim 7, characterized in that: The mass ratio of perovskite quantum dots, high molecular polymer and solvent in the coating solution is 0.1-0.6:20-100:80-60; and / or, the high molecular polymer in the coating solution comprises at least two different high molecular materials; And / or, the method for preparing the coating solution specifically comprises: mixing the perovskite quantum dots with a solvent to form a dispersion; The dispersion liquid is mixed with a high molecular polymer to form the coating liquid.

10. The preparation method according to claim 7, characterized in that: The heat treatment comprises a first treatment stage and a second treatment stage, wherein the temperature of the first treatment stage is 75-85° C. and the time is 20-40 min, and the temperature of the second treatment stage is 110-130° C. and the time is 15-25 min.

Citation Information

Patent Citations

  • Preparation method of LED quantum dot coating solution

    CN107394014A

  • A method for preparing LED quantum dot coating liquid

    CN107394014B

  • Perovskite type quantum dot film

    CN107966852A